2014
DOI: 10.1080/07399332.2014.908193
|View full text |Cite
|
Sign up to set email alerts
|

Cause of Death in Women of Reproductive Age in Rural Nepal Obtained Through Community-Based Surveillance: Is Reducing Maternal Mortality the Right Priority for Women's Health Programs?

Abstract: We used a community surveillance system to gather information regarding pregnancy outcomes and the cause of death for women of reproductive age (WRA) in Kanchanpur, Nepal. A total of 784 mother groups participated in the collection of pregnancy outcomes and mortality data. Of the 273 deaths among WRA, the leading causes of death reported were chronic diseases (94, 34.4%) poisoning, snake bites, and suicide (grouped together; 55, 20.1%), and accidents (29, 10.6%), while maternal mortality accounted for 7%. Neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…However, studies have also indicated that suicidal ideation may be higher in camps prior to migration where one study reported that, among women who screened positive for a common mental disorder, 91 % reported having had thoughts of suicide in the previous month [14]. Recent reports in Nepal identified suicide as the leading cause of death amongst women of reproductive age [21, 40]. Further investigation found mixed relationships between caste and suicide where more deaths occurred among higher castes, but more suicidal thoughts were endorsed in lower castes [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have also indicated that suicidal ideation may be higher in camps prior to migration where one study reported that, among women who screened positive for a common mental disorder, 91 % reported having had thoughts of suicide in the previous month [14]. Recent reports in Nepal identified suicide as the leading cause of death amongst women of reproductive age [21, 40]. Further investigation found mixed relationships between caste and suicide where more deaths occurred among higher castes, but more suicidal thoughts were endorsed in lower castes [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent five-country study found that Nepal community and clinical populations had high rates of suicide ideation, but the lowest amounts of ideation disclosure and help-seeking following an attempt (Jordans, et al, 2017). This underscores the importance of further research on why suicidal thoughts are not disclosed, as well as a better understanding of perceived drivers and meanings of suicidal deaths in Nepal (Jordans, et al, 2017; Jordans, et al, 2014; Pyakurel, et al, 2015; Marahatta, et al, 2016; Pradhan, et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…In Nepal, snakebite is an important public health problem [ 18 20 ] with peak annual incidence and mortality rates of up to 1162/100 000 and 162/100 000, respectively, reported in eastern regions [ 19 ]. Snakebite is a disease of poverty.…”
Section: Introductionmentioning
confidence: 99%